Fundamentals of financial instruments : an introduction to stocks, bonds, foreign exchange, and derivatives - Parameswaran, Sunil K., 1964- (Wiley finance series., 2022)
In the newly revised Second Edition of Fundamentals of Financial Instruments: An Introduction to Stocks, Bonds, Foreign Exchange, and Derivatives, renowned finance trainer Sunil Parameswaran delivers a comprehensive introduction to the full range of financial products commonly offered in the financial markets. Using clear, worked examples of everything from basic equity and debt securities to complex instruments--like derivatives and mortgage-backed securities - the author outlines the structure and dynamics of the free-market system and explores the environment in which financial instruments are traded. This one-of-a-kind book also includes: New discussions on interest rate derivatives, bonds with embedded options, mutual funds, ETFs, pension plans, financial macroeconomics, orders and exchanges, and Excel functions for finance Supplementary materials to enhance the reader's ability to apply the material contained within A foundational exploration of interest rates and the time value of money Fundamentals of Financial Instruments is the ideal resource for business school students at the undergraduate and graduate levels, as well as anyone studying financial management or the financial markets. It also belongs on the bookshelves of executive education students and finance professionals seeking a refresher on the fundamentals of their industry.